AJAS 2018
DOI: 10.16929/ajas/301.217
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictors of Inflation in Nigeria: BMA and WALS Techniques

Abstract: Abstract. The recent economic conundrum arising from the fall in the international oil price has threatened the maintenance of price stability, a key function of the central bank, therefore the need to investigate predictors of inflationary measures arises. The model averaging method considers uncertainty as part of the model selection, and include information from all candidate models. We analysed a wide spectrum of inflation predictors and all possible models for Nigeria CPI inflation using the Bayesian Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It was found that certain versions of DMA prediction quality are higher than that of the naïve forecasting model. The methodology for the BMA [12][13][14]15,16,17,18,19] and DMA techniques investigate the important variables in a model selection process, and are presented in the next section of the paper.…”
Section: Original Research Articlementioning
confidence: 99%
“…It was found that certain versions of DMA prediction quality are higher than that of the naïve forecasting model. The methodology for the BMA [12][13][14]15,16,17,18,19] and DMA techniques investigate the important variables in a model selection process, and are presented in the next section of the paper.…”
Section: Original Research Articlementioning
confidence: 99%